Optimization of Near and Far Field Patterns in de InxGa1-xN Lasers - Martín, Juan A.; Mon, Elis; Sánchez, M. (Revista Cubana de Física; Vol 26 No 2A (2009): XI Symposium and IX Congress of the Cuban Physical Society, and International Symposium "Physics in the 150th Anniversary of Max Planck's Birth", 2009)
In this work, the influence of the thickness of the n and p - GaN layers over near and far field patterns is analyzed for In x Ga 1-x N multiquantum well (MQW) laser structures. Two different optical cavities were considered, the conventional step separate confinement heterostructure (SCH-recta) and a graded-index (GRIN-SCH) structure with a parabolic variation of the Al content in the Al x Ga 1-x N guide layers. We found that for specific combinations of the thicknesses of the GaN layers the undesired ripples in the near and far-field patterns due to the insufficient Al x Ga 1-x N cladding layer thickness can be eliminated, being this an alternative solution to the problem to growth thick Al x Ga 1-x N cladding layers with higher aluminium content (x > 0.13).